1993
DOI: 10.1095/biolreprod49.3.496
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiodic Responses Differ among Inbred Strains of Golden Hamsters (Mesocricetus Auratus)1

Abstract: Inbred strains of golden hamsters differ in both the free-running period of the circadian rhythm of locomotor activity in constant darkness, and in the phase angle of entrainment of activity to a 14L:10D cycle. To determine whether these differences in circadian entrainment affect photoperiodic time measurement, we measured the critical photoperiod for maintaining testicular function as well as the rate of response for four different inbred strains (MHA/SsLak, LSH/SsLak, BIO 1.5, and BIO 87.20) and an outbred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The mutation might also have affected the gonadal response by altering gonadal sensitivity to pituitary hormones, or photoperiodic effects on FSH levels might be critical in determining testicular mass [31]. Additionally, strain differences between the wild-type Wrights and Charles River taus may have contributed to the differences observed between genotypes: different strains of normal inbred laboratory hamsters are reported to exhibit different rates of response to photoperiod, although these were apparently not attributable to genetic differences in circadian rhythmicity [32]. Nevertheless, it remains a possibility that had the study continued for one or two more weeks, the subtle differences observed between the two genotypes in response to the 6.67-h infusion of melatonin may not have been significant.…”
Section: Discussionmentioning
confidence: 99%
“…The mutation might also have affected the gonadal response by altering gonadal sensitivity to pituitary hormones, or photoperiodic effects on FSH levels might be critical in determining testicular mass [31]. Additionally, strain differences between the wild-type Wrights and Charles River taus may have contributed to the differences observed between genotypes: different strains of normal inbred laboratory hamsters are reported to exhibit different rates of response to photoperiod, although these were apparently not attributable to genetic differences in circadian rhythmicity [32]. Nevertheless, it remains a possibility that had the study continued for one or two more weeks, the subtle differences observed between the two genotypes in response to the 6.67-h infusion of melatonin may not have been significant.…”
Section: Discussionmentioning
confidence: 99%
“…However, the pineal produces melatonin also under LD and there is evidence that the target tissues are indeed quite able to decode the melatonin message (193,195). More importantly, the difference between a constantly active gonadotroph axis and a permanently inactive one is only a matter of minutes, as demonstrated by experiments aimed at the identification of the critical PP, which is of 12.5 h (197–199). This appears to hardly be compatible with the desensitisation hypothesis.…”
Section: The Seasonal Reproductive Cycles Of the Golden Hamster And Smentioning
confidence: 99%
“…Long photoperiods result in an increase in pituitary gonadotrophin secretion and activation of the gonads (Elliott 1976;Stetson & Tate-Ostro¡ 1981;Hastings et al 1989;Vitaterna & Turek 1993). In contrast, short photoperiods or continuous darkness (DD) initially causes the suppression of gonadotrophins and prolactin, and gonadal atrophy (Gaston & Menaker 1967;Berndtson & Desjardins 1974;Steger et al 1982;Vitaterna & Turek 1993;Stirland et al 1996a). However, after approximately 10^12 weeks, photo-inhibited animals undergo spontaneous recrudescence of the neuroendocrine axis and gonadal regrowth occurs, even during photoperiods which initially caused reproductive suppression (Stetson et al 1977;Turek & Campbell 1979;Reiter 1980).…”
Section: Introductionmentioning
confidence: 99%
“…During such cycles, tau mutants are unable to undergo gonadal regression in response to short photoperiods, even as short as 1 h of light per 24 h (1L:23D; Menaker & Re¢netti 1993). For wild-type hamsters, the equivalent photoperiod at which gonadal regression occurs is approximately 12L:12D or less (Elliott 1976;Hastings et al 1989;Vitaterna & Turek 1993;Stirland et al 1996a). In contrast, tau mutants kept on 20-h L:D cycles exhibit a normal photoperiodic response, undergoing full testicular regression at photoperiods of 10L:10D or less (Stirland et al 1996a).…”
Section: Introductionmentioning
confidence: 99%